2022
DOI: 10.3390/foods11040548
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and Microbiological Analysis of Spices and Aromatic Herbs

Abstract: Spices and aromatic herbs have always had great historical importance in human nutrition. Their use has been documented for centuries as a rich source of bioactive compounds; they have been used for their health benefits and also for flavoring or coloring food. However, despite the many health properties linked to the use of spices and aromatic herbs, these can represent biological hazards and can contain chemical substances of concern. Certainly, monitoring potential health hazards in spices and aromatic herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…These foods generally undergo drying processes at ambient temperature at the place of production. Moreover, in the developing countries from which they originate, harvesting and production technologies do not necessarily comply with optimal sanitary conditions [29][30][31]. The non-compliance with hygienic measures at all stages of the process, particularly during agricultural production, harvesting, washing and sun-drying, may explain the results of this study.…”
Section: Discussionmentioning
confidence: 82%
“…These foods generally undergo drying processes at ambient temperature at the place of production. Moreover, in the developing countries from which they originate, harvesting and production technologies do not necessarily comply with optimal sanitary conditions [29][30][31]. The non-compliance with hygienic measures at all stages of the process, particularly during agricultural production, harvesting, washing and sun-drying, may explain the results of this study.…”
Section: Discussionmentioning
confidence: 82%
“…The use of medical plants has been demonstrated to be useful in hematological malignancies, and this fact is undoubtedly arousing because every day clinicians in hematology and oncology units are confronted with the adverse effects of traditional drugs, which can sometimes cause the stop of the treatment if it is intolerable for patients and dangerous for their health [ 57 , 58 , 59 , 60 , 61 ]. Scientific research showed the efficacy of different natural compounds both in the prevention and cure of cancer [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Allegra and colleagues [ 33 ] studied the effects of rosemary in various types of cancer and put in evidence its action in augmenting antioxidant molecules, decreasing pro-inflammatory cytokines and preventing neo-vascularization, all functions crucial for the insurgence and progression of a tumor in general.…”
Section: Cinnamon and Hematological Malignanciesmentioning
confidence: 99%
“…For the screening of inorganic elements in breast samples, every sample (0.5 g) was added with 7 mL of HNO 3 and 1 mL of H 2 O 2 , and subsequently mineralized through a microwave digestion system (Ethos 1, Milestone, Bergamo, Italy), by raising the temperature from 0-200 • C in 10 min (hold time 10 min), with a microwave power of 1200 W. After a proper dilution in ultrapure water, the digested sample was analyzed by a quadrupole ICPMS iCAP Q (Thermo Scientific, Waltham, MA, USA), according to a method of anal-ysis previously optimized to reduce spectral (polyatomic and isobaric) and non-spectral interferences, according to what already described in our previous works [51][52][53][54][55][56]. The screening of minerals (i.e., Na, Mg and K), trace essential elements (i.e., Mn, Fe, Cu, Zn and Se), and potentially toxic elements (i.e., As, Cd and Pb) was performed according to a procedure reported elsewhere [57][58][59].…”
Section: Profile Of Inorganic Elementsmentioning
confidence: 99%